The scandalous neglect of children's mental health : what schools can do - Kauffman, James M.; Badar, Jeanmarie (New York : Routledge, Taylor & Francis Group, 2018)
'The Scandalous Neglect of Children's Mental Health: What Schools Can Do makes the case for the under-identification and under-service of children with mental health needs, both in special education and outside of it. After reading this brief but powerful book, you will better understand the need for expanded services for children and the nature of mental health needs. The risks and benefits of treatment, especially early intervention, are discussed in detail and guidelines for judging students' needs are provided. The sad fact that many people do not understand is that most young people with mental health needs never receive any treatment at all'--
Includes index.
Keywords: Mentally ill children -- Education -- United States; Mentally ill children -- Services for -- United States; Child mental health services -- United States; Psychotherapy